HCF164 Encodes a Thioredoxin-Like Protein Involved in the Biogenesis of the Cytochrome b(6)f Complex in Arabidopsis - Lennartz, Katja (American Society of Plant Biologists, 2001)
To understand the biogenesis of the plastid cytochrome b(6)f complex and to identify the underlying auxiliary factors, we have characterized the nuclear mutant hcf164 of Arabidopsis and isolated the affected gene. The mutant shows a high chlorophyll fluorescence phenotype and is severely deficient in the accumulation of the cytochrome b(6)f complex subunits. In vivo protein labeling experiments indicated that the mutation acts post-translationally by interfering with the assembly of the complex. Because of its T-DNA tag, the corresponding gene was cloned and its identity confirmed by complementation of homozygous mutant plants. HCF164 encodes a thioredoxin-like protein that possesses disulfide reductase activity. The protein was found in the chloroplast, where it is anchored to the thylakoid membrane at its lumenal side. HCF164 is closely related to the thioredoxin-like protein TxlA of Synechocystis sp PCC6803, most probably reflecting its evolutionary origin. The protein also shows a limited similarity to the eubacterial CcsX and CcmG proteins, which are required for the maturation of periplasmic c-type cytochromes. The putative roles of HCF164 for the assembly of the cytochrome b(6)f complex are discussed.